CLINICAL STUDY ON EFFECT OF DIFFERENT METHODS OF SHIRODHARA IN PATIENTS OF INSOMNIA - Patil, *Vasant; Godkar, Yogesh; Gupta, Sanjay; Das, K.C.; Kendadamath, D.B (International Journal of Ayurveda and Pharma Research, 2017)
Background: Insomnia has a great impact on social, occupational and other functioning areas of the individual. The modern medical science is still not having a definitive and effective treatment for this disease. Shirodhara is considered as the highly effective treatment for this condition. Most practitioners practising oscillatory method of Shirodhara, Some advises to do single point Shirodhara. Interestingly there is no research has been done on this topic to find out which method is best and standard. Aims: To compare the efficacy of single point drip method Jaladhara and Oscillatory drip method Jaladhara in Nidranasha. Methods and Materials: Study was conducted in 30 diagnosed patient of Nidranasha with the help of symptoms of nidranasha and Athens insomnia scale. The patients were randomly divided into 2 groups. i.e., Group A and Group B to compare the effect of Single point drip method and oscillatory drip method in Insomnia. Results: Group B (Oscillatory drip method Shirodhara) compared to Group A (Single point drip method Shirodhara) provided better relief clinically in subjective parameters Total sleep duration (48.3%), overall quality of sleep (48.3%) and Statistically provided moderately significant improvement in Functioning (physical and mental) and highly significant improvement in systolic blood pressure. Conclusion: Oscillatory drip method Shirodhara compared to Single point drip method Shirodhara provided better relief clinically and statistically.